How Green Are the Public Libraries of Tehran? - Zahra Hassanian; Atefeh Sharif; Behnaz Bagherpour; Zainab Sabbaghi Bidgoli (International Journal of Information Science and Management)
Libraries and information centers are one of the main pillars of sustainable development and include various dimensions such as green building, green management, green services, green information systems, and green resources. The environmental tasks of green libraries are not limited to having a green building but also include educating and promoting sustainability through appropriate information resources. The present study evaluates the public libraries of Tehran based on green public libraries and green information management indicators. This paper is an applied study that employs a survey approach. The study population comprised all the librarians and managers of public libraries of Tehran during the years 2019-2020. There were 168 people, out of which 118 people were randomly selected. The data collection tool was a researcher-made questionnaire, including green library indicators and green information management. The validity of the questionnaire was confirmed by the face validity method, and its reliability was determined using Cronbach's alpha test of 0.864. Data were analyzed using Chi-square, one-sample t-test, pair t-test, and Friedman tests. The findings of the study indicate that 20 out of 28 indicators for assessing the status of using the indicators of green public libraries are in a position above average with 95% confidence; Of these, 3 indicators are above 90%, 3 indicators are above 80%, 7 indicators are above 70%, 7 indicators are above 50%, 6 indicators are above 30%, and 4 indicators are below 30%. The results of this part of the study can be generalized to the statistical population with 95% confidence according to the Chi-square test results. The current status of green information management in public libraries in Tehran is lower than average and does not have a good status. Components of culture building, planning, developing online and remote services, human resource management and development, acquisition and resource sharing, information dissemination and raising awareness, collaboration with other green organizations, using eco-friendly equipment, and evaluation of information and services have obtained ranks 1-9 respectively in the current state of green information management. There is a significant difference between the current and desired status of each component of green information management. The most significant mean difference is related to human resource management and development, collaboration with other green organizations, developing online and remote services, evaluation of information and services, planning, and using eco-friendly equipment. The results of this study show that the level of compliance of public libraries in Tehran with green management indicators is not satisfactory and is lower than the average. Most of the activities in the field of green management in libraries are the result of the individual efforts of librarians and decentralized programs rather than organizational efforts. From the point of view of green information management, the public libraries of Tehran city are in an inappropriate situation and the need for culture building in this field is felt.